Respuesta :

[tex]\bf A= \begin{bmatrix} -3&5&-6\\9&-5&3 \end{bmatrix}\qquad \qquad B= \begin{bmatrix} -2&6&7\\2&-1&-6 \end{bmatrix}\\\\ -------------------------------\\\\ -3A= \begin{bmatrix} 9&-15&18\\-27&15&-9 \end{bmatrix}\qquad \qquad 6B= \begin{bmatrix} -12&36&42\\12&-6&-36 \end{bmatrix}\\\\ -------------------------------\\\\ -3A+6B\implies \begin{bmatrix} 9-12&\qquad -15+36&\qquad 18+42\\ -27+12&\qquad 15-6&\qquad -9-36 \end{bmatrix} \\\\\\ -3A+6B\implies \begin{bmatrix} -3&21&60\\ -15&9&-45 \end{bmatrix}[/tex]
ACCESS MORE